Teaching kindergarteners creativity with "OCCUT": Origami paper - Rani Darmayanti; Choirudin Choirudin (Kepompong Children Centre Journal, 2023)
One of the objectives of the kindergarten curriculum is to enhance originality or creativity. Children's creativity in kindergarten can be optimized through educational media. This study aims to provide a comprehensive account of the planning, execution, progress, and challenges educators encounter in utilizing origami paper as an instructional tool at the Assyfa Learning Center (YALC) Pasuruan Foundation Kindergarten. The present study employs descriptive research methodologies, adopting a qualitative approach. The research sample consisted of two educators and ten preschool-aged children. The findings derived from the data analysis indicate that the planning and implementation executed by teachers exhibit a commendable level of quality. In contrast, children's creative growth manifests in diverse ways through their output. This activity encompasses many intriguing conditions, prompting an examination of the child's state during its execution.